UPAYA KYAI DALAM MENINGKATKAN KEMAMPUAN SANTRI DALAM MEMBACA KITAB KUNING DI PONDOK PESANTREN ANNIDA AL-ISLAMY BEKASI (Studi Kualitatif Naturalistik di Pondok Pesantren Annida Al-Islamy Bekasi) - Soleh Slamet; Siti Asiah (Turats, 2021)
This study aims to determine the efforts of the leaders of Islamic boarding schools in improvingthe ability of students to read the yellow book at the Annida Al-Islamy Islamic boarding school Bekasi.This study aims to determine the response of the santri to the kyai’s efforts in improving the ability toread the yellow book at the Annida Al-Islamy Islamic boarding school, Bekasi. To find out what factorsare the supporting and inhibiting factors of the kyai’s efforts in improving the ability of students to readthe yellow book at the Annida Al-Islamy Islamic boarding school Bekasi. The benefits of this researchcan add insight and form a good person, a person who is faithful and pious and can appreciate thelegacy of the scholars of the past and present. This study uses the Naturalistic Qualitative method,namely research that is based on a phenomenological view and seeks to understand the meaning ofevents and their relationships to the object of research. The result is descriptive data, in the form ofwritten words, sentences and oral and observable behavior, so that it can produce the intended overall.The results of this study indicate that, KH. Muhammad Aiz as the leader of the Annida Al-IslamyIslamic boarding school has made good efforts to improve the ability of his students to read the yellowbook, he even went down to teach the yellow book to his students with the bandongan method whichwas created, and the shorogan method is still used mainly for For new students, the nahwu and shoroflessons are highly emphasized to the students to be studied seriously, using the bandongan, soroganand rote methods. With systematic and serious efforts made by kyai and ustadz who are in charge ofteaching the students, this has been successfully done, and what is targeted can be achieved, namelythat students are able to read the yellow book properly and correctly.